Peculiarities in the language's use of terminology and professions (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article is about the issue of the methodology of linguistic research and use of terminology and professional terms in the language. The most conceptually important issue not only in Uzbek linguistics, but also in foreign linguistics. Systematic linguistics, which follows the principle of "from specifics to generalities" formed at the end of the 19th century and the beginning of the 20th century, works on the basis of direct observation of specifics and differences, compares them with each other, and aims to reveal common aspects. Systematic study of language was a great achievement of 20th century linguistics. The peculiarity of these studies is that they do not approach linguistic facts autonomously, but pay attention to the discovery of the hidden essence of each linguistic phenomenon. The researcher's attention is more focused on elucidating the relationship between linguistic phenomena.